Patentamiento de anticuerpos monoclonales: El caso de Argentina - Juan Correa; Catalina de la Puente; Ramiro Picasso; Constanza Silvestrini (South Centre, 2023)
– This research paper aims to identify, describe and analyze the patents on monoclonal antibodies granted by the National Institute of Industrial Property (INPI) of Argentina, from 2010 to 2020 inclusive. The research includes the protected subject matter and the universe of applicants, among other aspects. To this end, a database of patents and applications was created, where the characteristics of the patent applications and granted patents, ownership and nationality of the applicants, status of the applications, the time it takes to process a patent application and divisional patents are examined. The document also presents recommendations on public policy applicable to the examination of patent applications on monoclonal antibodies.
Keywords: 300; Access to Medicines; Argentina; Biologicals; Biologics; Biopharmaceuticals; Biosimilars; Intellectual Property; Monoclonal Antibodies; Patent; Public Health